Agreement restrictions - D'Alessandro, Roberta; Fischer, Susann; Hrafnbjargarson, Gunnar Hrafn (Interface explorations, 2008)
This book brings together scholars who have been working on agreement restrictions within the generative framework. The articles range from syntactic to morphological approaches, investigating different domains of agreement restrictions, such as the Person Case Constraint, nominative objects, and Quirky Case Restrictions in a series of European and Non-European languages, providing new data and novel analyses for both, new and well-known facts. This book collects different and relevant studies in this field and gives a general overview of the different theoretical approaches concerned with the morphological, syntactic and semantic properties of agreement restriction phenomena.
Keywords: Grammar, Comparative and general : Agreement; Language and languages : Grammars; Syntax, semantics, interface, agreement